The Importance and Shaping Methods of Psychological Capital Management for College Physical Education Teachers - Xin Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to explore the importance and shaping methods of psychological capital management for college physical education teachers. At present, "psychological capital" is becoming more and more popular, and has been applied in human resources, management and other fields. Psychological capital is an important non Physical capital, which can generate a huge driving force for individual attitudes and behaviors. The author conducted a questionnaire survey on university teachers and studied their psychological capital and work engagement. The results of descriptive statistical analysis show that the psychological capital and work engagement of primary school teachers are generally at a low level. Descriptive statistical analysis shows that the psychological capital and work investment of university teachers are generally at a low level. There are significant differences in psychological capital, job engagement, and other aspects among university teachers of different types of schools, professional titles, and monthly salaries. The research results show a significant positive correlation between work engagement and psychological capital. Strengthen incentives for the development of college students' psychological capital, clarify the research content of college students' psychological capital development, and broaden the channels for college students' psychological capital development.